(untitled) (Journal of Management, 2020)
Happiness is the ultimate goal of human life which can be achieved through positivity. Positivity fosters internal strengths, provides happiness and wellbeing. This article aims to deal about self-management as a tool of positive psychology. It highlights the components of self-management which provides the sense of positivity in achieving individuals working and life goal. It focuses on understanding the factors for making the human life worthy. It attempts to define the positive psychology and establishes connection between positive psychology and self-management. It has taken some quotations from the holy book Bhagvat Gita to justify the content of self-management.